Multi-metallic contamination around former uranium mines induces adverse effects and acclimation disturbance in three-spined stickleback (Gasterosteus aculeatus) - A. Le Guernic; W. Sanchez; S. Betoulle; B. Gagnaire (MDPI AG, 2014)
Not available